Exogenous Abscisic Acid Mimics Cold Acclimation for Cacti Differing in Freezing Tolerance. - Loik, M. E. (1993)
The responses to low temperature were determined for two species of cacti sensitive to freezing, Ferocactus viridescens and Opuntia ficus-indica, and a cold hardy species, Opuntia fragilis. Fourteen days after shifting the plants from day/night air temperatures of 30/20[deg]C to 10/0[deg]C, the chlorenchyma water content decreased only for O. fragilis. This temperature shift caused the freezing tolerance (measured by vital stain uptake) of chlorenchyma cells to be enhanced only by about 2.0[deg]C for F. viridescens and O. ficus-indica but by 14.6[deg]C for O. fragilis. Also, maintenance of high water content by injection of water into plants at 10/0[deg]C reversed the acclimation. The endogenous abscisic acid (ABA) concentration was below 0.4 pmol g-1 fresh weight at 30/20[deg]C, but after 14 d at 10/0[deg]C it increased to 84 pmol g-1 fresh weight for O. ficus-indica and to 49 pmol g-1 fresh weight for O. fragilis. Four days after plants were sprayed with 7.5 x 10-5 M ABA at 30/20[deg]C, freezing tolerance was enhanced by 0.5[deg]C for F. viridescens, 4.1[deg]C for O. ficus-indica, and 23.4[deg]C for O. fragilis. Moreover, the time course for the change in freezing tolerance over 14 d was similar for plants shifted to low temperatures as for plants treated with exogenous ABA at moderate temperatures. Decreases in plant water content and increases in ABA concentration may be important for low-temperature acclimation by cacti, especially O. fragilis, which is widely distributed in Canada and the United States.